Transplantation after Mustard operation for transposition of the great arteries - Shintaro Katahira (Wiley, 2021)
Abstract As long‐term outcomes of congenital heart diseases improve, the probability of adult patients presenting for heart transplantation for late failure of congenitally corrected heart disease also increases. In patients with dextro‐transposition of the great arteries (d‐TGA) who were initially treated in the era of Mustard or Senning procedures and before Jatene procedure was introduced, progressive systemic right ventricular failure represents a problem in the very long‐term follow‐up. We report a rare case of heart transplantation as a third operation 36 years after Mustard procedure in a patient with d‐TGA experiencing late failure of the systemic right ventricle.